Ángel Crespo, La vida plural de Fernando Pessoa, Barcelona, Seix Barral, 2007, 414 pp. - Merchán Ruiz, Juan Carlos (Estudios Humanísticos. Filología, 2008)
Ángel Crespo, La vida plural de Fernando Pessoa, Barcelona, Seix Barral, 2007, 414 pp.